Yum Yummy Yuck - Jones, Cree Lane; Jones, Amanda Jane (New York, NY : Prestel, 2019)
Simple text and illustrations help babies and toddlers learn to avoid putting certain things into their mouths, including boogers, coins, and crayons.
Cover title.
On board pages.
Keywords: Food -- Juvenile fiction; Food -- Fiction; Board books; Board books; Board books; Picture books